2013
DOI: 10.28945/1895
|View full text |Cite
|
Sign up to set email alerts
|

Access or Egress? Questioning the “Ethics” of Ethics Committee Review for an Ethnographic Doctoral Research Study in a Childbirth Setting

Abstract: In this article, we discuss the principal difficulties in gaining ethics approval for an ethnographic midwifery doctoral research project in a hospital setting in South Australia. The research focus is on the various personal, social, institutional and cultural influences on women making a choice about whether or not to use epidural analgesia in labour. The obstacles encountered in gaining human research ethics committee (HREC) approval are discussed within the wider context of the benefits of ethnography as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Other ethnographic studies have similarly reported that this method has brought insight into cultural norms in the hospital maternity system (Newnham et al . ). To obtain this data in the hospital setting, there were challenges that needed to be overcome.…”
Section: Implications For Video Ethnographic Researchmentioning
confidence: 97%
See 2 more Smart Citations
“…Other ethnographic studies have similarly reported that this method has brought insight into cultural norms in the hospital maternity system (Newnham et al . ). To obtain this data in the hospital setting, there were challenges that needed to be overcome.…”
Section: Implications For Video Ethnographic Researchmentioning
confidence: 97%
“…, Newnham et al . ) and attended the ethics committee meetings to promote confidence in their research (Simmons ). With persistence and continued communication, ethics approval can be achieved.…”
Section: Implications For Video Ethnographic Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Consent during the participant observation on labour ward was assumed, with well-disseminated information about the study and researcher disclosure. Staff could opt-out of the research by signing a written opt-out form but no-one availed of this (see Newnham et al, 2013). All midwives verbally consented to the presence of the researcher in their antenatal class and the researcher was introduced as such to the class participants.…”
Section: Introductionmentioning
confidence: 99%
“…Written consent was gained from the women who participated in the study. Consent for the site observation was more difficult to obtain and this has been discussed elsewhere (Newnham, Pincombe, & McKellar, 2013). Once Newnham had access to the field, hospital staff were widely informed and given the opportunity to opt out.…”
Section: Introductionmentioning
confidence: 99%